Perbedaan Kemampuan Literasi Sains dengan Menggunakan Pembelajaran Kooperatif Tipe Jigsaw dan Group Investigation - Yena Harnita; Tomi Hidayat; Apriza Fitriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to describe students' scientific literacy skills in Biology learning through the application of cooperative learning models: Jigsaw, Group Investigation, and conventional methods. The method used was an experimental study with a posttest-only control group design. The results showed that there was no significant difference in scientific literacy skills among Grade X students of SMA Negeri 9 Kaur across the three learning models, based on ANOVA and LSD tests with a significance level of α > 0.05. The average scores of students’ scientific literacy were Jigsaw class = 35, Group Investigation class = 34.091, and conventional class = 30.909. In conclusion, the application of Jigsaw, Group Investigation, and conventional learning models did not result in a significant difference in students’ scientific literacy skills. Keywords: Scientific Literacy Skills, Biology Learning